Effectiveness of a classification-based approach to low back pain in primary care - a benchmarking controlled trial - Anna Sofia Simula; Antti Malmivaara; Neill Booth; Jaro Karppinen (Medical Journals Sweden, 2024)
Objective: The aim of this study was to assess the effectiveness of classification-based approach for low back pain care in Finnish primary care. Design: A benchmarking controlled trial design was used. Subjects/patients: Three primary healthcare areas and 654 low back pain patients with or without sciatica. Methods: Classification-based care (using the STarT Back Tool) was implemented using organizational-, healthcare professional-, and patient-level interventions. The primary outcome was change in Patient-Reported Outcomes Measurement Information System, Physical Function (PROMIS PF-20) from baseline to 12 months. Results: No difference was found between the intervention and control in change in PROMIS PF-20 over the 12-month follow-up (mean difference 0.33 confidence interval -2.27 to 2.9, p = 0.473). Low back pain-related healthcare use, imaging, and sick leave days were significantly lower in the intervention group. Reduction in intensity of low back pain appeared to be already achieved at the 3-month follow-up (mean difference -1.3, confidence interval -2.1 to -0.5) in the intervention group, while in the control group the same level of reduction was observed at 12 months (mean difference 0.7, confidence interval -0.2 to 1.5, treatment*time p = 0.003).  Conclusion: Although classification-based care did not appear to influence physical functioning, more rapid reductions in pain intensity and reductions in healthcare use and sick leave days were observed in the intervention group.